A rhenium-ruthenium synergistically reinforced ti(c,n)-based cermet tool material and a preparation method thereof

CN122687023BActive Publication Date: 2026-10-30SUZHOU LABORATORY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611194887.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-30
Estimated Expiration
2046-08-07

AI Technical Summary

Technical Problem

[0007]为解决现有Ti(C,N)基金属陶瓷刀具材料中Co/Ni粘结相高温软化导致性能急剧恶化,以及Re固溶强化时易偏聚脆化、Ru强化效果温和且两者缺乏协同利用方案,难以同时提升高温硬度、高温强度与室温断裂韧性的问题,本发明提供了一种铼钌协同强化的Ti(C,N)基金属陶瓷刀具材料,在Ti(C,N)基金属陶瓷的Co/Ni粘结相体系中,将微量Re和微量Ru按特定比例、特定方式引入,能够产生显著的协同效应,不仅可显著提升Ti(C,N)基金属陶瓷高温强度和硬度,且可保持其室温断裂韧性不降低甚至有所提升,使得该铼钌协同强化的Ti(C,N)基金属陶瓷刀具材料能够适用于高速切削难加工材料的刀具制造

Benefits of technology

本发明通过在粘结相中同时引入微量的Re、Ru元素,并精确控制Re与Ru的质量比(1:1-3:1),利用Ru对Re微观偏聚的抑制效应,在极少量贵金属添加下即实现显著的固溶强化;同时,高能机械合金化预处理使Re、Ru原子在固态下即过饱和固溶于Co-Ni基体,从源头消除了元素分布不均,并在后续烧结中促使粘结相与硬质相形成更均匀、细密的显微组织及强界面结合。得益于成分与工艺的协同,本发明提供的刀具料在800 ℃高温硬度较传统Ti(C,N)基金属陶瓷大幅提升的同时,室温断裂韧性保持较高水平,有效克服了增硬降韧的共性难题,并兼具优异的组织均匀性和性能稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122687023B_ABST
    Figure CN122687023B_ABST
Patent Text Reader

Abstract

The application relates to a rhenium-ruthenium synergistically reinforced Ti(C, N) based cermet tool material and a preparation method thereof. The material comprises the following raw material components in parts by mass: Ti(C, N) powder 40-60 parts, composite binder phase 25-40 parts, and metal carbide 15-25 parts. The composite binder phase is composed of cobalt, nickel, rhenium and ruthenium. During preparation, the cobalt, nickel, rhenium and ruthenium elemental powders are subjected to high-energy mechanical alloying pretreatment to obtain a uniformly solid-solution composite binder phase, and then the Ti(C, N) powder and the metal carbide are mixed and sintered, and the 1430-1500 DEG C liquid phase sintering can effectively inhibit the microsegregation of Re, fully play the solid solution strengthening of Re and the homogenization synergistic effect of Ru, and simultaneously improve the high-temperature hardness, high-temperature strength and room-temperature fracture toughness of the material. The obtained cermet still maintains excellent mechanical properties at 800 DEG C, and is particularly suitable for the manufacture of tools for high-speed cutting of difficult-to-machine materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of metal ceramics and powder metallurgy, specifically to a rhenium-ruthenium synergistically strengthened Ti(C,N)-based metal ceramic cutting tool material. Background Technology

[0002] Ti(C,N)-based cermets are composite materials prepared using powder metallurgy, with Ti(C,N) as the hard phase and Co / Ni or other metals as the binder phase. These materials combine the high hardness and wear resistance of ceramics with the strength and toughness of metals, and exhibit good chemical stability, making them widely used as high-speed cutting tool materials. However, with the increasing application of difficult-to-machine materials such as high-temperature alloys and hardened steels in industries like aerospace, energy equipment, and mold manufacturing, higher demands are being placed on the high-temperature performance of tool materials. During high-speed cutting, the local temperature at the tool tip can reach over 800 °C. At this temperature, the Co / Ni binder phase in traditional Ti(C,N)-based cermets softens rapidly, leading to a significant decrease in the bonding strength between the hard phase particles. This drastically deteriorates the tool's wear resistance and resistance to plastic deformation, severely restricting the improvement of cutting efficiency and the extension of tool life.

[0003] To improve the high-temperature performance of Ti(C,N)-based cermets, a great deal of research has been conducted, mainly focusing on the following directions: One approach is to strengthen the binder phase through solid solution by adding elements such as Cr, Mo, and W. These elements can improve the high-temperature strength of the binder phase to some extent, but the strengthening effect is limited, and a large amount of these elements can affect the wettability of the binder phase to the hard phase.

[0004] Secondly, the overall high-temperature performance of the material can be improved by refining the grains through optimizing the carbon-nitrogen ratio and particle size of the Ti(C,N) hard phase, or by adding cubic carbides such as TaC and NbC. However, these methods mainly optimize the hard phase framework and have limited effect on improving the core problem of high-temperature softening of the binder phase.

[0005] At the academic research level, while some literature reports that rhenium (Re) has a significant solid solution strengthening effect on Co / Ni-based alloys, which can greatly improve the high-temperature mechanical properties of the alloys, some researchers have also explored adding ruthenium (Ru) to cemented carbide systems to improve the microstructure stability of the binder phase. However, Re has limited solid solubility in the binder phase, and excessive addition can lead to embrittlement of the binder phase; while the strengthening effect of Ru is relatively mild, and its improvement in high-temperature strength when added alone is limited.

[0006] Therefore, how to simultaneously improve high-temperature hardness and room-temperature toughness in Ti(C,N)-based cermet systems remains a technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0007] To address the issues of drastic performance degradation caused by high-temperature softening of the Co / Ni binder phase in existing Ti(C,N)-based cermet cutting tool materials, the tendency for Re solid solution strengthening to segregate and become embrittled, the mild strengthening effect of Ru, and the lack of synergistic utilization of both, making it difficult to simultaneously improve high-temperature hardness, high-temperature strength, and room-temperature fracture toughness, this invention provides a rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material. By introducing trace amounts of Re and Ru into the Co / Ni binder phase system of Ti(C,N)-based cermet in a specific ratio and manner, a significant synergistic effect can be achieved. This not only significantly improves the high-temperature strength and hardness of Ti(C,N)-based cermet but also maintains its room-temperature fracture toughness without reduction or even improves it. Therefore, this rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material is suitable for manufacturing cutting tools for high-speed cutting of difficult-to-machine materials.

[0008] Specifically, the following technical solutions are provided: The first aspect of this invention provides a rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material, comprising the following raw material components by mass parts: 40-60 parts of Ti(C,N) powder, 25-40 parts of a composite binder phase, and 15-25 parts of a metal carbide; wherein the composite binder phase is obtained by high-energy mechanical alloying pretreatment of a mixture of Co, Ni, Re, and Ru powders, wherein the amount of Re element added is 1-3 parts, the amount of Ru element added is 0.5-2 parts, and the mass ratio of Re element to Ru element is (1-3):1.

[0009] Through the synergistic effect of the aforementioned material selection (Re-Ru compositional synergy) and process optimization (high-energy mechanical alloying pretreatment), a Ti(C,N)-based cermet cutting tool material with high room temperature fracture toughness, excellent high-temperature hardness, and high-temperature strength was obtained. The synergistic mechanism is specifically manifested in the following two closely related aspects: (1) Re-Ru Synergy: In the binder phase, Re and Ru form a complementary pair of strong solid solution strengthening and homogenization diffusion. Among them, trace amounts of Re provide strong solid solution strengthening, significantly improving the room temperature and high temperature deformation resistance of the binder phase; trace amounts of Ru play a homogenization diffusion role, inhibiting the micro-segregation of Re during sintering and cooling, avoiding local embrittlement of the binder phase, while Ru can slow down the atomic diffusion rate at high temperature, inhibiting the grain growth of the hard phase, thus improving the high temperature performance retention rate from multiple dimensions. When the amount of Re added is 1-3 parts and the amount of Ru added is 0.5-2 parts, and the mass ratio of Re to Ru is strictly controlled at (1-3):1, the two achieve the best balance between solid solution strengthening effect and segregation suppression ability, maximizing the strengthening contribution of Re and giving full play to the lubrication and slowing growth effect of Ru, producing a significant synergistic effect, thereby maintaining the toughness-strength matching of the binder phase and the fine grain structure of the hard phase in a wide temperature range.

[0010] (2) Synergistic Process-Composition Coupling: In this invention, the mixed powder of Co, Ni, Re, and Ru is pretreated by high-energy mechanical alloying. Through repeated cold welding-fracture-re-welding processes, Re and Ru atoms are uniformly dispersed in the Co-Ni matrix in the solid state, forming a supersaturated pre-alloyed solid solution. This step eliminates the macroscopic and microscopic segregation caused by differences in melting point and density during the mixing of traditional elemental powders from the source, significantly advancing the task of element homogenization that originally required long-term diffusion during liquid-phase sintering. In the subsequent liquid-phase sintering process, the pre-alloyed binder phase only needs to undergo a very short high-temperature holding period to achieve compositional homogenization, significantly compressing the time window for Re migration and agglomeration in the liquid phase, further reducing the risk of Re agglomeration, fully releasing the solid solution strengthening potential of Re, and simultaneously improving the interfacial bonding strength between the binder phase and the hard phase. Therefore, it can be seen that process pretreatment not only ensures the effective realization of the Re-Ru synergistic effect, but also shortens the high-temperature process, reduces the driving force of grain growth, and couples synergistically with the material composition, so that the tool material has excellent deformation resistance, microstructure stability and interfacial bonding strength under high-temperature cutting conditions.

[0011] In some embodiments of the present invention, the microstructure of the above-mentioned Ti(C,N)-based cermet cutting tool material consists of hard phase particles and a metal-based composite binder phase filling the spaces between the hard phase particles. The hard phase particles include first hard phase particles with a black core-gray shell structure and second hard phase particles with a white core-gray shell structure.

[0012] In some embodiments of the present invention, the average particle size of the above-mentioned Ti(C,N) powder is preferably 0.5-2 μm, such as 0.5 μm, 1 μm, 1.5 μm, 2 μm, etc.; more preferably, the N / (C+N) atomic ratio in the above-mentioned Ti(C,N) powder is 0.4-0.7, so as to ensure that the hard phase has good comprehensive performance.

[0013] In some embodiments of the present invention, the amount of Co added in the above-mentioned composite binder phase is 15-25 parts, and the amount of Ni added is 10-18 parts.

[0014] In some embodiments of the present invention, the preparation of the above-mentioned composite binder phase includes the following steps: weighing Co, Ni, Re, and Ru elemental powders according to the ratio, and performing high-energy ball milling under an inert atmosphere (e.g., argon) to obtain a uniformly dissolved composite binder phase powder; preferably, a planetary high-energy ball mill is used for ball milling, wherein in the above-mentioned high-energy ball milling step: the ball milling medium is cemented carbide balls, the ball-to-material ratio is (10-15):1, the ball milling speed is 350-450 rpm, and the ball milling time is 20-40 h; more preferably, during the high-energy ball milling process, the machine is stopped for 15 min every 1 h of ball milling to prevent the powder from overheating and oxidizing, and finally a pre-alloyed powder with refined grains and uniform elemental solution is obtained.

[0015] In this invention, by combining pre-mechanical alloying of the binder phase with a specific Re-Ru ratio, the industry problem of Re element's tendency to segregate and become embrittled is solved at its source. Compared with the process of directly adding elemental powder, the pre-alloying treatment can further increase the material's high-temperature hardness at 800℃ by more than 10%, while maintaining or even improving its room-temperature fracture toughness.

[0016] In some embodiments of the present invention, the metal carbide is selected from at least two of WC, Mo2C, TaC, and NbC. By adding an appropriate amount of metal carbide, the wettability of the binder phase to the hard phase is improved, and the abnormal growth of the hard phase grains during the sintering process is suppressed.

[0017] In this invention, the types and proportions of other carbides are adapted to the Re / Ru synergistic binder phase, preferably a combination of at least two of WC, Mo2C, TaC, and NbC, with a content of 15-25 parts by mass. This adaptation design ensures that during liquid-phase sintering, the carbides can effectively inhibit the growth of hard phase grains, forming an ideal core-ring structure, while maintaining good interfacial bonding with the Re / Ru-containing binder phase. This avoids interfacial weakening caused by compositional mismatch, resulting in positive synergy among the components and further amplifying the effect of Re / Ru addition on the overall performance improvement of the material.

[0018] The second aspect of this invention provides a method for preparing the rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material described in the first aspect, specifically including the following steps: S1. Weigh out Ti(C,N) powder, composite binder phase, metal carbide and dispersant according to the ratio and wet-mill to mix them to obtain a mixed slurry; S2. The mixed slurry obtained in step S1 is dried. The dried material is mixed evenly with the molding agent and then sprayed to obtain intermediate particles. S3. Press the intermediate particles obtained in step S2 into a molding process to obtain a green body; S4. The green blank obtained in step S3 is subjected to vacuum sintering treatment, the vacuum sintering treatment including the liquid phase sintering step, to obtain the Ti(C,N)-based cermet cutting tool material; the liquid phase sintering temperature is 1430-1500 ℃, for example 1430 ℃, 1440 ℃, 1450 ℃, 1460 ℃, 1470 ℃, 1480 ℃, 1490 ℃, 1500 ℃, etc., and the time is 1-2 hours.

[0019] In the above preparation method, this invention, through extensive experimental screening, determined a precise liquid-phase sintering temperature window of 1430-1500 °C, coupled with a holding time of 1-2 hours. This sintering regime forms a deep synergy with the composite binder phase obtained through high-energy mechanical alloying pretreatment. Within this temperature window, the binder phase fully melts into a liquid phase. Re and Ru have suitable diffusion rates and solubilities in the liquid phase, enabling the remaining local micro-homogenization migration. Simultaneously, sufficient densification can be achieved with short-term holding (1-2 h), allowing Ti(C,N) and metal carbides to form an ideal core-ring structure through dissolution-reprecipitation. More importantly, this precise temperature and time control effectively preserves the uniform solid solution state brought about by pre-alloying. The short liquid phase presence significantly compresses the thermodynamic time window for Re re-segregation at grain boundaries / phase boundaries, while the high-temperature duration is insufficient to induce Ostwald ripening and growth of the hard phase, thus avoiding grain coarsening. Subsequently, slow cooling in the furnace freezes this molecular-level uniform solid solution distribution within the binder phase. Therefore, in this invention, pre-alloying and liquid phase sintering at 1430-1500 ℃ for 1-2 h form a deep synergy: the former provides the initial homogeneity foundation, while the latter transforms this foundation into the final fine-grained, strong, and thermally stable microstructure through precise temperature and time control. Both are indispensable and together ensure that the tool material has excellent room temperature and high temperature performance.

[0020] In some embodiments of the present invention, in step S1, the dispersant includes anhydrous ethanol, and the ratio of the total mass of Ti(C,N) powder, composite binder phase, and metal carbide to the amount of dispersant added is 1:(1.1-1.5), for example 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, etc.

[0021] In some embodiments of the present invention, in step S1, the ball milling media used for wet milling is cemented carbide balls, the ball-to-material ratio is (5-7):1, the wet milling speed is 200-300 rpm, and the wet milling time is 24-48 h.

[0022] In some embodiments of the present invention, in step S2, the drying temperature is 75-90 ℃, the molding agent is paraffin or polyethylene glycol, and the mass ratio of the dried material to the molding agent is 1:(0.02-0.03).

[0023] In some embodiments of the present invention, in step S3, the pressure in the pressing step is 150-250 MPa.

[0024] In some embodiments of the present invention, in step S4, the vacuum sintering process includes sequentially performing a first solid-phase sintering, a second solid-phase sintering, and a liquid-phase sintering step. In the first solid-phase sintering step, the temperature is raised to 400-600 ℃ at a heating rate of 0.5-2 ℃ / min and held for 1-2 h to remove the forming agent. In the second solid-phase sintering step, the temperature is raised to 1200-1300 ℃ at a heating rate of 1-3 ℃ / min and held for 0.5-1 h. In the liquid-phase sintering step, the temperature is raised to 1430-1500 ℃ at a heating rate of 2-4 ℃ / min and held for 1-2 h. Subsequently, the material is cooled in the furnace to obtain Ti(C,N)-based cermet cutting tool material.

[0025] The beneficial effects of this invention are as follows: This invention achieves significant solid solution strengthening with minimal addition of noble metals by simultaneously introducing trace amounts of Re and Ru elements into the binder phase and precisely controlling the mass ratio of Re to Ru (1:1-3:1). Utilizing the inhibitory effect of Ru on the microscopic segregation of Re, it achieves this strengthening through the simultaneous introduction of trace amounts of Re and Ru elements into the Co-Ni matrix. Simultaneously, high-energy mechanical alloying pretreatment ensures that Re and Ru atoms are supersaturated and dissolved in the Co-Ni matrix in the solid state, eliminating elemental unevenness at its source. This promotes a more uniform and dense microstructure and strong interfacial bonding between the binder and hard phases during subsequent sintering. Thanks to the synergy of composition and process, the tool material provided by this invention exhibits significantly improved hardness at 800 °C compared to traditional Ti(C,N)-based cermets, while maintaining high room-temperature fracture toughness. This effectively overcomes the common problem of hardening while reducing toughness, and also possesses excellent microstructure uniformity and performance stability.

[0026] Through extensive experimental screening, this invention has determined that 1430-1500 ℃ is the key liquid phase sintering temperature window for achieving Re / Ru synergistic strengthening, coupled with a holding time of 1-2 hours and a slow cooling regime in the furnace. These process conditions ensure the full diffusion and uniform distribution of Re and Ru atoms in the binder melt, ultimately forming a stable synergistic solid solution structure. At the same time, the process parameters are clear, highly controllable, and have good batch-to-batch consistency, making it suitable for large-scale stable production.

[0027] The entire preparation process of this invention is completed under only one thermal cycle condition. The process route is simple and requires no special equipment. Ordinary vacuum sintering furnaces can meet the production requirements, which significantly reduces equipment investment and manufacturing costs. At the same time, this simple and controllable process is conducive to rapid industrialization and provides an economical and reliable technical path for the mass production of high-performance metal ceramic cutting tool materials. Attached Figure Description

[0028] Figure 1 A scanning electron microscope (SEM) backscattered electron image of the polished surface of the rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet tool material of Example 1; Figure 2 Comparison of room temperature hardness, room temperature fracture toughness, and high temperature hardness of Ti(C,N)-based cermet cutting tool materials prepared in various embodiments and comparative examples; Figure 3 The graph shows a comparison of the room temperature bending strength and high temperature bending strength of the Ti(C,N)-based cermet cutting tool materials prepared in each embodiment and comparative example. Detailed Implementation

[0029] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The terms “comprising” or “including” used in this invention may also be replaced with the closed form “is” or “consisting of”.

[0031] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the data analysis is performed using conventional statistical analysis methods. Unless otherwise specified, the reagents and materials used are commercially available or prepared by known methods.

[0032] The Ti(C,N) powder used in the following examples and comparative examples was purchased from Zhuzhou Haokun Hard Materials Co., Ltd.

[0033] Example 1: This example relates to the preparation of a rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material, which comprises the following raw material components in parts by mass: Ti(C 0.7 N 0.3 55 parts of Co powder (average particle size 1.2 μm), 6 parts of WC powder, 9 parts of Mo2C powder, and 36 parts of composite binder phase (obtained by high-energy mechanical alloying pretreatment of 20 parts of Co powder, 13.5 parts of Ni powder, 1.5 parts of Re powder, and 1.0 parts of Ru powder, wherein the mass ratio of Re to Ru is 1.5:1).

[0034] The specific steps are as follows: (1) Preparation of composite binder phase: Co, Ni, Re and Ru elemental powders were weighed according to the ratio, loaded into a cemented carbide ball mill jar, and then evacuated and filled with high-purity argon for protection. A planetary high-energy ball mill was used with a ball-to-material ratio of 12:1, a rotation speed of 400 rpm, and a ball milling time of 30 h. The mill was stopped and cooled for 15 min after every 1 h of ball milling to obtain composite binder phase powder.

[0035] Ingredient preparation and ball milling: Weigh the raw material powders according to the above proportions and place them in a planetary ball mill for wet grinding. The grinding balls are cemented carbide balls, with a ball-to-material ratio of 6:1. The wet grinding speed is 250 rpm, and the wet grinding time is 36 hours. The wet grinding medium is anhydrous ethanol, added at 1.2 times the weight of the mixture. A uniform slurry is obtained after ball milling.

[0036] (2) Drying and granulation: The mixed slurry obtained in step (1) is dried in an infrared drying oven at 80 °C, and then 2.5 wt% of paraffin wax is added as a molding agent to perform spray granulation to obtain mixed powder particles with uniform particle size.

[0037] (3) Press molding: The mixed powder particles obtained in step (2) are pressed into shape under a pressure of 200 MPa to obtain the tool blank.

[0038] (4) Vacuum sintering: The green blank obtained in step (3) is placed in a vacuum sintering furnace. First, the temperature is raised to 550 ℃ at a heating rate of 1 ℃ / min and held for 1.5 hours to remove the forming agent. Then, the temperature is raised to 1250 ℃ at a heating rate of 2 ℃ / min and held for 45 minutes for solid-phase sintering. Finally, the temperature is raised to 1480 ℃ at a heating rate of 3 ℃ / min and held for 1.5 hours for liquid-phase sintering. Then, the furnace is cooled to room temperature to obtain the rhenium-ruthenium synergistic strengthening Ti(C,N) based cermet cutting tool material.

[0039] Figure 1 The image shows a scanning electron microscope (SEM) backscattered electron image of the polished surface of the rhenium-ruthenium synergistically reinforced Ti(C,N)-based cermet tool material prepared in this embodiment. As can be seen from the image, the microstructure of the cermet tool material obtained in this embodiment consists of hard phase particles with black core-gray shell and white core-gray shell structures and a metal matrix composite binder phase, and the microstructure is uniform and dense.

[0040] Example 2: This example relates to the preparation of a rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material, which comprises the following raw material components by mass parts: Ti(C 0.5 N 0.552 parts of powder (average particle size 1.5 μm), 8 parts of WC powder, 6 parts of TaC powder, 3 parts of NbC powder, and 35.8 parts of composite binder phase (obtained by high-energy mechanical alloying pretreatment of 19 parts of Co powder, 14 parts of Ni powder, 2.0 parts of Re powder and 0.8 parts of Ru powder, wherein the mass ratio of Re to Ru is 2.5:1).

[0041] The specific steps are as follows: (1) Preparation of composite binder phase: Co, Ni, Re and Ru elemental powders were weighed according to the ratio, loaded into a cemented carbide ball mill jar, and then evacuated and filled with high-purity argon for protection. A planetary high-energy ball mill was used with a ball-to-material ratio of 10:1, a rotation speed of 450 rpm, and a ball milling time of 20 h. The mill was stopped and cooled for 15 min after every 1 h of ball milling to obtain composite binder phase powder.

[0042] Ingredient preparation and ball milling: Weigh the raw material powders according to the above proportions and place them in a planetary ball mill for wet grinding. The grinding balls are cemented carbide balls, with a ball-to-material ratio of 5:1. The wet grinding speed is 300 rpm, and the wet grinding time is 24 hours. The wet grinding medium is anhydrous ethanol, added at 1.1 times the weight of the mixture. A uniform slurry is obtained after ball milling.

[0043] (2) Drying and granulation: The mixed slurry obtained in step (1) is dried in an infrared drying oven at 90 °C, and then 2.0 wt% of paraffin wax is added as a molding agent to perform spray granulation to obtain mixed powder particles with uniform particle size.

[0044] (3) Press molding: The mixed powder particles obtained in step (2) are pressed into shape under a pressure of 250 MPa to obtain the tool blank.

[0045] (4) Vacuum sintering: The green blank obtained in step (3) is placed in a vacuum sintering furnace. First, the temperature is raised to 400 ℃ at a heating rate of 0.5 ℃ / min and held for 2 hours to remove the forming agent. Then, the temperature is raised to 1200 ℃ at a heating rate of 1 ℃ / min and held for 60 minutes for solid-phase sintering. Finally, the temperature is raised to 1500 ℃ at a heating rate of 2 ℃ / min and held for 1 hour for liquid-phase sintering. Then, the furnace is cooled to room temperature to obtain the rhenium-ruthenium synergistic strengthening Ti(C,N) based metal ceramic tool material.

[0046] Example 3: This example relates to the preparation of a rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material, which comprises the following raw material components in parts by mass: Ti(C 0.6 N 0.458 parts of powder (average particle size 0.8 μm), 10 parts of WC powder, 8 parts of NbC powder, 7 parts of Mo2C powder, and 32.2 parts of composite binder phase (obtained by high-energy mechanical alloying pretreatment of 18 parts of Co powder, 12 parts of Ni powder, 1.2 parts of Re powder and 1.0 parts of Ru powder, wherein the mass ratio of Re to Ru is 1.2:1).

[0047] The specific steps are as follows: (1) Preparation of composite binder phase: Co, Ni, Re and Ru elemental powders were weighed according to the ratio, loaded into a cemented carbide ball mill jar, and then evacuated and filled with high-purity argon for protection. A planetary high-energy ball mill was used with a ball-to-material ratio of 15:1, a rotation speed of 350 rpm, and a ball milling time of 40 h. The mill was stopped and cooled for 15 min after every 1 h of ball milling to obtain composite binder phase powder.

[0048] Ingredient preparation and ball milling: Weigh the raw material powders according to the above proportions and place them in a planetary ball mill for wet grinding. The grinding balls are cemented carbide balls, with a ball-to-material ratio of 7:1. The wet grinding speed is 300 rpm, and the wet grinding time is 48 hours. The wet grinding medium is anhydrous ethanol, added in an amount 1.5 times the weight of the mixture. A uniform slurry is obtained after ball milling.

[0049] (2) Drying and granulation: The mixed slurry obtained in step (1) is dried in an infrared drying oven at 75 °C, and then 3.0 wt% of paraffin wax is added as a molding agent to perform spray granulation to obtain mixed powder particles with uniform particle size.

[0050] (3) Press molding: The mixed powder particles obtained in step (2) are pressed into shape under a pressure of 150 MPa to obtain the tool blank.

[0051] (4) Vacuum sintering: The green blank obtained in step (3) is placed in a vacuum sintering furnace. First, the temperature is raised to 600 ℃ at a heating rate of 2 ℃ / min and held for 1 hour to remove the forming agent. Then, the temperature is raised to 1300 ℃ at a heating rate of 3 ℃ / min and held for 30 minutes for solid-phase sintering. Finally, the temperature is raised to 1430 ℃ at a heating rate of 4 ℃ / min and held for 2 hours for liquid-phase sintering. Then, the furnace is cooled to room temperature to obtain the rhenium-ruthenium synergistic strengthening Ti(C,N) based metal ceramic tool material.

[0052] Comparative Example 1: This comparative example relates to the preparation of a Ti(C,N)-based cermet cutting tool material, which comprises the following raw material components in parts by mass: Ti(C) 0.7 N 0.3 55 parts of powder (average particle size 1.2 μm), 6 parts of WC powder, 3 parts of Mo2C powder, and 36 parts of composite binder phase (composed of 22 parts of Co powder and 14 parts of Ni powder).

[0053] The only difference from Example 1 is that the composite binder phase does not contain Re and Ru, while the other operations are the same, and the corresponding Ti(C,N)-based cermet cutting tool material is prepared.

[0054] Comparative Example 2: This comparative example relates to the preparation of a Ti(C,N)-based cermet cutting tool material, which comprises the following raw material components in parts by mass: Ti(C) 0.7 N 0.3 55 parts of powder (average particle size 1.2 μm), 6 parts of WC powder, 3 parts of Mo2C powder, and 36 parts of composite binder phase (composed of 20 parts of Co powder, 12 parts of Ni powder, and 4 parts of Re powder).

[0055] The only difference from Example 1 is that the composite binder phase does not contain Ru, while the other operations are the same, and the corresponding Ti(C,N)-based cermet cutting tool material is prepared.

[0056] Comparative Example 3: This comparative example relates to the preparation of a Ti(C,N)-based cermet cutting tool material, which comprises the following raw material components in parts by mass: Ti(C) 0.7 N 0.3 55 parts of Co powder (average particle size 1.2 μm), 6 parts of WC powder, 3 parts of Mo2C powder, and 36 parts of composite binder phase (composed of 21 parts of Co powder, 12.5 parts of Ni powder, 2 parts of Re powder, and 0.5 parts of Ru powder, wherein the mass ratio of Re to Ru is 4:1).

[0057] The only difference from Example 1 is that the mass ratio of Re to Ru in the composite binder phase is different; all other operations are the same, and the corresponding Ti(C,N)-based cermet cutting tool material is prepared.

[0058] Comparative Example 4: This comparative example relates to the preparation of a Ti(C,N)-based cermet cutting tool material, which comprises the following raw material components in parts by mass: Ti(C) 0.7 N 0.3 55 parts of Co powder (average particle size 1.2 μm), 6 parts of WC powder, 3 parts of Mo2C powder, and 36 parts of composite binder phase (obtained by high-energy mechanical alloying pretreatment of 20 parts of Co powder, 13.5 parts of Ni powder, 1.5 parts of Re powder, and 1.0 parts of Ru powder, wherein the mass ratio of Re to Ru is 1.5:1).

[0059] The only difference from Example 1 is that the liquid phase sintering temperature in step (4) is 1400 °C and the holding time is 1.5 h. All other operations are the same, and the corresponding Ti(C,N) based metal ceramic cutting tool material is prepared.

[0060] Comparative Example 5: This comparative example relates to the preparation of a Ti(C,N)-based cermet cutting tool material, which comprises the following raw material components in parts by mass: Ti(C) 0.7 N 0.3 55 parts of Co powder (average particle size 1.2 μm), 6 parts of WC powder, 3 parts of Mo2C powder, and 36 parts of composite binder phase (obtained by high-energy mechanical alloying pretreatment of 20 parts of Co powder, 13.5 parts of Ni powder, 1.5 parts of Re powder, and 1.0 parts of Ru powder, wherein the mass ratio of Re to Ru is 1.5:1).

[0061] The only difference from Example 1 is that the liquid phase sintering temperature in step (4) is 1520 °C and the holding time is 1.5 h. All other operations are the same, and the corresponding Ti(C,N) based metal ceramic cutting tool material is prepared.

[0062] Comparative Example 6: This comparative example relates to the preparation of a Ti(C,N)-based cermet cutting tool material, which comprises the following raw material components in parts by mass: Ti(C) 0.7 N 0.3 55 parts of powder (average particle size 1.2 μm), 6 parts of WC powder, 3 parts of Mo2C powder, 20 parts of Co powder, 13.5 parts of Ni powder, 1.5 parts of Re powder, and 1.0 part of Ru powder.

[0063] The only difference from Example 1 is that: in step (1), the composite binder phase is not prepared, and all the raw materials are directly mixed according to the ratio and then wet-milled. The rest of the operations are the same, and the corresponding Ti(C,N) based metal ceramic cutting tool material is prepared.

[0064] Comparative Example 7: This comparative example relates to the preparation of a Ti(C,N)-based cermet cutting tool material, which comprises the following raw material components in parts by mass: Ti(C) 0.7 N 0.3 55 parts of powder (average particle size 1.2 μm), 6 parts of WC powder, 3 parts of Mo2C powder, and 36 parts of composite binder phase (obtained by high-energy mechanical alloying pretreatment of 20 parts of Co powder, 13.5 parts of Ni powder, 1.5 parts of Cr powder, and 1.0 parts of Ru powder, wherein the mass ratio of Cr to Ru is 1.5:1).

[0065] The only difference from Example 1 is that an equal amount of Cr powder is used to replace Re powder, while all other operations are the same, and the corresponding Ti(C,N)-based cermet cutting tool material is prepared.

[0066] The process parameters and operations for preparing Ti(C,N)-based cermet cutting tool materials in the above embodiments and comparative examples are summarized in Table 1 below: Table 1

[0067] In the table, √ indicates a step that includes mechanical alloying pretreatment, and × indicates a step that does not include mechanical alloying pretreatment, where the binder phase components are directly mixed with other components.

[0068] Performance testing The following mechanical property tests were performed on the Ti(C,N)-based cermet cutting tool materials prepared in the above embodiments and comparative examples: (1) Hardness test: The room temperature Rockwell hardness was measured according to GB / T 3849.1-2015 standard, and the 800 ℃ high temperature hardness was measured according to GB / T 230.1-2018 standard; (2) Bending strength test: The room temperature bending strength was measured in accordance with GB / T 3851-2015 standard, and the high temperature bending strength at 800 ℃ was measured in accordance with GB / T 14390-2008 standard; (3) Fracture toughness test: Fracture toughness is measured in accordance with the standard GB / T33819-2017.

[0069] The test results are summarized in Table 2 below: Table 2

[0070] From Table 2 and Figure 2 , Figure 3 It can be seen that the Ti(C,N)-based cermet cutting tool materials prepared by combining Re and Ru with mechanical alloying pretreatment in Examples 1-3 exhibit excellent comprehensive mechanical properties and high-temperature stability. Among them, Example 1 achieves the best balance in various indicators, not only with a room temperature hardness of up to 1180 HV, but also with an ultra-high bending strength of 2568 MPa and a tensile strength of 19.5 MPa·m. 1 / 2 The material exhibits excellent fracture toughness and maintains a hardness of 565 HV and a bending strength of 1850 MPa even at 800 ℃. All these properties are significantly superior to those of Ti(C,N)-based cermet cutting tools prepared without the addition of Re and Ru (Comparative Example 1). Although the fracture toughness of Examples 2 and 3 decreased with increasing sintering temperature and composition adjustment, their overall performance was still significantly better than the comparative examples without Re / Ru or with improper processing, fully demonstrating the superiority of this material system in achieving a synergistic improvement in high strength, high toughness, and high-temperature resistance.

[0071] As demonstrated in Example 1 and Comparative Examples 2 and 3, the synergistic addition of Re and Ru significantly enhances the material's properties. Comparative Example 2, although containing Re, lacked Ru and had a high Re content, resulting in a significant decline in both room temperature and high temperature mechanical properties. In particular, the flexural strength at 800 °C plummeted to 979 MPa, indicating that adding Re alone with an unbalanced ratio cannot achieve the optimal strengthening effect. Furthermore, in Comparative Example 3, the Re / Ru mass ratio was as high as 4:1, with a severely insufficient Ru content, leading to increased brittleness and a drop in room temperature flexural strength to 1749 MPa. High-temperature performance also deteriorated sharply, further confirming that Re and Ru need to be maintained within a reasonable mass ratio range to achieve synergistic effects.

[0072] As shown in Examples 1 and Comparative Examples 4-6, the liquid phase sintering temperature and mechanical alloying pretreatment process significantly affect the mechanical properties of Ti(C,N)-based cermet cutting tool materials. The sintering temperature of Comparative Example 4 was only 1400 °C. Due to insufficient densification during sintering, its room temperature flexural strength and high temperature flexural strength decreased to 1549 MPa and 539 MPa, respectively, demonstrating that appropriate high-temperature sintering is crucial for obtaining a dense microstructure and excellent properties. Conversely, the sintering temperature of Comparative Example 5 was too high, reaching 1520 °C, leading to defects such as abnormal grain growth, causing a complete collapse of the material's mechanical properties. The room temperature flexural strength was only 1294 MPa, and the high-temperature flexural strength at 800 °C was even lower at 229 MPa, indicating that excessively high sintering temperatures severely impair the material's strength and toughness. Furthermore, Comparative Example 6 did not undergo mechanical alloying pretreatment, and its room temperature and high-temperature flexural strengths were significantly lower than those of Example 1, indicating that mechanical alloying can effectively promote the uniform mixing and activation of powders and is an indispensable process for improving the overall performance of the material.

[0073] As demonstrated by Examples 1 and 7, Ru exhibits significant advantages over Cr in the binder phase system of this invention. Comparative Example 7 used Cr instead of Re in Example 1. Although the Ru content and sintering process were maintained, its room temperature flexural strength was 2005 MPa and its high-temperature flexural strength at 800 °C was 1110 MPa, both significantly lower than those of Example 1. This indicates that in the binder phase of Ti(C,N)-based cermets, a specific combination of Re and Ru provides superior strengthening and toughening effects compared to the combination of Cr and Ru in improving metal / ceramic interface wettability, refining grain size, and enhancing high-temperature thermal stability.

[0074] In summary, this invention has successfully prepared a Ti(C,N)-based cermet cutting tool material with excellent comprehensive performance by organically combining pre-mechanical alloying of the binder phase with Re-Ru synergistic proportioning and precise sintering process, achieving a simultaneous and significant improvement in the high-temperature hardness, high-temperature strength and room-temperature toughness of Ti(C,N)-based cermet.

[0075] The above-described embodiments are merely preferred embodiments provided to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the claims.

Claims

1. A rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material, characterized in that, It contains the following raw material components by mass parts: 40-60 parts Ti(C,N) powder, 25-40 parts composite binder phase, and 15-25 parts metal carbide; The composite binder phase is obtained by high-energy mechanical alloying pretreatment of mixed powders of Co, Ni, Re and Ru, wherein the amount of Re added is 1-3 parts, the amount of Ru added is 0.5-2 parts, and the mass ratio of Re to Ru is (1-3):

1. The preparation method of the rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material includes the following steps: S1. Weigh out Ti(C,N) powder, composite binder phase, metal carbide and dispersant according to the ratio and wet-mill to mix them to obtain a mixed slurry; S2. The mixed slurry obtained in step S1 is dried. The dried material is mixed evenly with the molding agent and then sprayed to obtain intermediate particles. S3. Press the intermediate particles obtained in step S2 into a molding process to obtain a green body; S4. The green blank obtained in step S3 is subjected to vacuum sintering treatment, the vacuum sintering treatment including the step of liquid phase sintering, to obtain the Ti(C,N) based metal ceramic tool material; the liquid phase sintering temperature is 1430-1500 ℃, and the time is 1-2 h.

2. The rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material according to claim 1, characterized in that, The microstructure of the Ti(C,N)-based cermet cutting tool material consists of hard phase particles and a metal-based composite binder phase filling the spaces between the hard phase particles. The hard phase particles include first hard phase particles with a black core-gray shell structure and second hard phase particles with a white core-gray shell structure.

3. The rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material according to claim 1, characterized in that, The average particle size of the Ti(C,N) powder is 0.5-2 μm; And / or, the N / (C+N) atomic ratio in the Ti(C,N) powder is 0.4-0.

7.

4. The rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material according to claim 1, characterized in that, Preparation of the composite binder phase The process includes the following steps: Weigh out elemental powders of Co, Ni, Re, and Ru according to the specified ratio, and perform high-energy ball milling under an inert atmosphere to obtain a uniformly solid-solid composite binder phase powder; In the high-energy ball milling step: the milling medium is cemented carbide balls, the ball-to-material ratio is (10-15):1, the milling speed is 350-450 rpm, and the milling time is 20-40 h.

5. The rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material according to claim 1, characterized in that, The metal carbide is selected from at least two of WC, Mo2C, TaC, and NbC.

6. A method for preparing a rhenium-ruthenium synergistically strengthened Ti(C,N)-based cermet cutting tool material as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Weigh out Ti(C,N) powder, composite binder phase, metal carbide and dispersant according to the ratio and wet-mill to mix them to obtain a mixed slurry; S2. The mixed slurry obtained in step S1 is dried. The dried material is mixed evenly with the molding agent and then sprayed to obtain intermediate particles. S3. Press the intermediate particles obtained in step S2 into a molding process to obtain a green body; S4. The green blank obtained in step S3 is subjected to vacuum sintering treatment, the vacuum sintering treatment including the step of liquid phase sintering, to obtain the Ti(C,N) based metal ceramic tool material; the liquid phase sintering temperature is 1430-1500 ℃, and the time is 1-2 h.

7. The preparation method according to claim 6, characterized in that, In step S1, the dispersant is anhydrous ethanol; And / or, the ratio of the total mass of the Ti(C,N) powder, the composite binder phase, and the metal carbide to the amount of the dispersant added is 1:(1.1-1.5). And / or, in the wet milling mixing step: the milling media are cemented carbide balls, the ball-to-material ratio is (5-7):1, the wet milling speed is 200-300 rpm, and the wet milling time is 24-48 h.

8. The preparation method according to claim 6, characterized in that, In step S2, the drying temperature is 75-90 ℃; And / or, the molding agent is paraffin or polyethylene glycol; And / or, the mass ratio of the dried material to the molding agent is 1:(0.02-0.03).

9. The preparation method according to claim 6, characterized in that, In step S3, during the pressing and molding process, the pressure is 150-250 MPa.

10. The preparation method according to claim 6, characterized in that, In step S4, the vacuum sintering process includes sequential solid-phase sintering, a second solid-phase sintering, and a liquid-phase sintering step. In the first solid-phase sintering step: the temperature is increased to 400-600 ℃ at a heating rate of 0.5-2 ℃ / min and held for 1-2 h; In the second solid-phase sintering step: the temperature is increased to 1200-1300 ℃ at a heating rate of 1-3 ℃ / min and held for 0.5-1 h; In the liquid phase sintering step: the temperature is increased to 1430-1500 ℃ at a heating rate of 2-4 ℃ / min and held for 1-2 h.

Citation Information

Patent Citations

  • High-strength and high-toughness metal ceramic and preparation method thereof

    CN118880144A